Correlation between Troponin I Level and Major Adverse Cardiovascular Events (MACE) in Patients with Acute Myocardial Infarction at Gotong Royong Hospital Surabaya - Lenny Kartika Sari; Winda Diah Nugraheni (Syntax Idea)
Acute coronary syndromes (ACS) are critical medical emergencies that can disrupt the progression of coronary artery disease at any given time. Cardiac troponin I levels are precise and sensitive markers for detecting acute myocardial infarction (AMI). Assessing the incidence of Major Adverse Cardiovascular Events (MACE) in patients experiencing AMI is pivotal for guiding medical interventions. This study investigates the association between cardiac troponin I levels and the frequency of MACE in individuals diagnosed with AMI. Employing an observational analytic approach with a cross-sectional design, the research focuses on patients diagnosed with AMI, including both ST-segment elevation myocardial infarction (STEMI) and non-ST-segment elevation myocardial infarction (NSTEMI), admitted to Gotong Royong Hospital in Surabaya from January to December 2023. The relationship between troponin I level and MACE was examined through bivariate analysis using the Chi-square test within SPSS 23.0 software. Among the 76 participants, the majority were aged over 65 years (39.5%), with 51 males (67.1%), and 59 patients were diagnosed with NSTEMI (77.6%). MACE occurred in 39 individuals (51.4%) with AMI, notably including heart failure in 69.2% of cases. Regarding cardiac troponin I (cTnI) values, 17 patients had STEMI, while 59 were diagnosed with NSTEMI. Within the AMI group, 6.6% were classified in Group 1, 26.3% in Group 2, and 67.1% in Group 3. Remarkably, a significantly higher proportion of patients with MACE exhibited markedly elevated cTnI levels in Group 3 (78.3%). In summary, the study highlights a significant association between cardiac troponin I levels and the occurrence of major adverse cardiovascular events (MACE) in patients with acute myocardial infarction at Gotong Royong Hospital in Surabaya.